Sifat Kuat Tarik Dan Morfologi Termoplastik Elastomer Dari Komposit Polypropylene & Natural Rubber - Indah Agus Setiorini (Jurnal Teknik Patra Akademika, 2017)
This research was conducted in order to develop TPE products that have been produced become prime material and can be accepted by the automotive and medical equipment industry. Thermoplastic elastomers produced are based on Polypropylene and natural rubber for industrial use. The method used in this study was Polypropylene grafting process with Maleic Anhydride (PP-g-MA). The grafting process was carried out at the temperature of 160°C and a time of 10 minutes. The variations in the composition of PP/NR/CB are (70:30:0) % by weight, (69:30:1) % by weight, (68:30:2) % by weight and (67:30:3) % by weight. The characteristic test which was conducted included the surface morphology and elongation at break. The obtained results showed that the mechanical test in the form of tensile strenght kept increases as the level of filler increased. The best value was obtained from tensile strenght obtained from the composite ratio of NR/PP/CB (67:30:3) % by weight was 1,66 N/mm3.